Assessment of Urban public spaces: Cases of Kuala Lumpur city center / Amir Hossein Askari - Askari, Amir Hossein (2014)

(untitled)
Public open spaces are vital elements of urban fabrics that animate communities in cities. They are appropriate spaces for performing cultural gathering or declaring political freedom. These significant places provide people with different facilities as well as social and health-promoting opportunities. Successful public open spaces meet the needs of people of different social classes, ethnicities, and in general different backgrounds. These substantially beneficial spaces in cities endow urbanites with physical, social, and psychological comfort. Investigating the visions of the City Hall Kuala Lumpur shows that the City Center lacks successful public open spaces that meet users’ needs. Therefore, the main question raised in this research is ‘what are the components of a successful public open space in the City Center of Kuala Lumpur?’ This research aims to enhance the quality of public life in the City Center of Kuala Lumpur through identifying the characteristics of a sociably successful public open space. The research employed a quantitative approach. Accordingly, the self-administered questionnaire surveys collected the data. The sampling method used was the mix of systematic and time-interval methods. Followed by that, the structure interviews with Landscape Architects, Academicians, and Town Planners verified the results of the public surveys and assisted the research in reaching the methodological triangulation. The findings showed that the public facilities play a more significant role in attracting people to the public open spaces than social and health-promoting benefits. The research disclosed that old people prefer passive activities such as sitting, talking to their friends, and watching people, while young people do activities and explore the places and mingle with both their peers and others. The findings uncovered that the physical, personal, managerial, iv and social factors influence social interactions in the public open spaces of the City Center of Kuala Lumpur. In summary, the physical factors, meanings attached, social activities and events, inclusiveness and social interactions, and design features are the urban factors contributing to the creation of a successful public open space. Overall, the findings of this research are beneficial to designers in choosing the factors to ameliorate the viability of social interactions among different groups of urban dwellers. This assists them in determining the features and characteristics of successful public open spaces that enliven the public life in City Centers.